Analisis Pengaruh Struktur Modal, Ukuran Perusahaan, dan Likuiditas terhadap Kinerja Keuangan Industri Mamin 2019–2023 - Maya Tika Zulkarnain; Wastam Wahyu Hidayat; Supardi Supardi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of capital structure, company size, and liquidity on the financial performance of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The food and beverage industry is one of the sectors that has a significant contribution to national economic growth, so understanding the factors that affect its financial performance is crucial. The method used is a quantitative approach with multiple linear regression analysis techniques to test the relationships between variables. The data used comes from the annual financial statements of companies that are included in the sub-sector for the past five years. The results of the study show that partially, the capital structure has a significant influence on the company's financial performance, which is shown by a calculated t-value of 6.414 and a significance value of 0.000 (< 0.05). These findings indicate that the more optimal the capital structure managed by the company, the better its financial performance. On the other hand, company size and liquidity do not show a significant influence on financial performance. The company size has a t-value of -1.493 with a significance of 0.140 (> 0.05), while liquidity has a t-value of 0.765 with a significance of 0.447 (> 0.05). However, simultaneously, these three independent variables together have a significant effect on financial performance, as shown by a calculated F-value of 19,527 and a significance value of 0.000 (< 0.05). The results of this study provide important implications for company management to pay more attention to the management of capital structure, as it is the dominant factor in influencing financial performance. Optimizing capital structure can be used as a strategy to increase the efficiency and competitiveness of the company in the midst of the dynamics of the food and beverage industry.